Penerapan Kurikulum Merdeka Belajar dalam Meningkatkan Motivasi Belajar Matematika Siswa Kelas VII MTsN 3 Kuningan (Indo-MathEdu Intellectuals Journal, 2023)
The purpose of this research is to analyze the implementation of the independent curriculum on learning motivation. This research uses qualitative descriptive analysis. Research data collection techniques were carried out by filling out questionnaires and interviews. The subjects of this research were mathematics teachers and students of class VII 8 MTsN 3 Kuningan. The instruments used in this research were a motivation questionnaire sheet, an independent curriculum questionnaire sheet and an interview guide. The results of this research show that implementing an independent curriculum can increase student learning motivation. The existence of an independent curriculum is implemented by giving students freedom to explore their knowledge as widely as possible and providing space for exploration, increasing creativity and active participation which overall increases students' interest in learning mathematics